Les élections locales 2013 en Côte d’Ivoire : des malentendus subsistent sur l’exercice de la démocratie - Christian Bouquet; Irène Kassi-Djodjo (EchoGéo)
Installed in difficulty in May 2011, the new Ivorian regime managed to keep the electoral calendar of the 2010-2015 mandature. After the legislatives of December 2011, local elections (municipal and regional) took place in a calm in April 2013. Therefore, the democratic process has lugged the same weaknesses (incomplete list of electors, unrenowned independent electoral commission). In addition, the FIP (the party of former Head of State) has once more boycotted the consultations and many divisions inside the others two major parties (RDR and PDCI) have blurred their scores and gave to "independents" an electoral weight difficult to decipher. Fortunately, the issues were minimal due the fact that the decentralization is still largely virtual.